Morphological derivations and inflections in an Algerian Arabic dialect / Djaffar Farida - Farida, Djaffar (2013)
So far, not much research has been carried out on the morphological description of the Algerian Arabic dialect, applying the principles of modern structural linguistics. Algeria, a North African country, has many dialects spoken in the various regions of its vast geographical area, including non-Arabic dialects. This paper deals with one of these dialects, namely the Arabic Algiers Urban Dialect (AAUD). As the name indicates, it is the dialect of the capital city. This study focuses on the inflectional and derivational grammatical (morphological) formations found in the Algiers Arabic Urban dialect (AAUD), based on the systematic analysis, applying the Replacive Morpheme, Root-and-Pattern system, Item-and-Process (IP) and the Item-and-Arrangement morphological principles with suitable conditionings and illustrations. Though there are variations found within this dialect, no attempt has been made to stratify the differences due to social variables. The present paper presents the important aspects of different parts of speech in morphology, including nouns (and pronouns), verbs and adjectives. Since we are dealing with an Arabic dialect, a brief overview of the Standard Arabic language structure is presented first (with root and pattern system) along with definitions and exemplification. This is followed by the sections on verbal derivations and inflections. The sections dealing with nouns, adjectives, and pronouns follow consecutively.